2018
DOI: 10.1007/s00441-018-2868-0
|View full text |Cite
|
Sign up to set email alerts
|

The insulin receptor is differentially expressed in somatic and visceral primary sensory neurons

Abstract: Recent studies demonstrated the expression of the insulin receptor (InsR) and its functional interaction with the transient receptor potential vanilloid type 1 receptor (TRPV1) in primary sensory neurons (PSNs). The present study was undertaken to reveal the target-specific expression of the InsR and its co-localization with the TRPV1 in rat PSNs. We assessed the localization of the InsR and its co-localization with the TRPV1 in PSNs retrogradely labelled with biotin-conjugated wheat germ agglutinin injected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…The neurochemical phenotypes of InsR-expressing PSNs innervating different organs have also been revealed. It has been demonstrated that about one-quarter of somatic (cutaneous and muscle) and about half of visceral (urinary bladder and pancreatic) PSNs express the InsR [24]. In addition, it has been demonstrated that the differences between the two subpopulations (somatic and visceral) were significant [24].…”
Section: Neurochemical Characterization Of Somatic and Visceral Psns mentioning
confidence: 99%
See 3 more Smart Citations
“…The neurochemical phenotypes of InsR-expressing PSNs innervating different organs have also been revealed. It has been demonstrated that about one-quarter of somatic (cutaneous and muscle) and about half of visceral (urinary bladder and pancreatic) PSNs express the InsR [24]. In addition, it has been demonstrated that the differences between the two subpopulations (somatic and visceral) were significant [24].…”
Section: Neurochemical Characterization Of Somatic and Visceral Psns mentioning
confidence: 99%
“…It has been demonstrated that about one-quarter of somatic (cutaneous and muscle) and about half of visceral (urinary bladder and pancreatic) PSNs express the InsR [24]. In addition, it has been demonstrated that the differences between the two subpopulations (somatic and visceral) were significant [24]. However, about 60% of InsR-expressing PSNs innervating the dorsal hind paw skin, the gastrocnemius muscle, the urinary bladder and the pancreas showed TRPV1 receptor immunoreactivity [24].…”
Section: Neurochemical Characterization Of Somatic and Visceral Psns mentioning
confidence: 99%
See 2 more Smart Citations
“…Insulin exerts its neural actions through the insulin receptor (InsR), a member of the receptor tyrosine kinases family ( Ward and Lawrence, 2009 ) present in nerve tissue ( Havrankova et al, 1978 ; Unger et al, 1989 ). Further, it has also been revealed that a relatively high proportion of dorsal root ganglion (DRG) neurons express the InsR ( Baiou et al, 2007 ; Lázár et al, 2018a , b ).…”
Section: Introductionmentioning
confidence: 99%